Relax : Dealing with Stress - Watts, Murray, author 542912; Cooper, Cary L., author 417636 (London : BBC Books, 1992)
Aimed at all those who suffer from what Americans call "hurry sickness", this book looks at the most common upsets that people face in the course of their lives at home and at work, including the stress of first-time motherhood and coping with the loss of a job. It even advises on averting the frayed tempers of drivers sitting in a traffic jam. Although based on Professor Cooper's scientific studies, the book presents his advice in a straightforward way, to help readers work out the likely causes of stress in their lives and use the recommended methods to deal with it. His other books include "Understanding Executive Stress" and "Stress at Work".